The Effect of a Proposed Training Program on Developing Some Physical Fitness Components for Swimming Coaches - Akour, Ahmad Abed Alwahab; Akour, Mohammed (Journal of Posthumanism, 2025)
This research investigates the influence of a structured, scientifically designed training program on the motor response speed of swimming coaches, a key physical component crucial for water safety. Given that swimming coaches often double as lifeguards in aquatic environments, enhancing their physical capabilities is vital for improving response time during emergencies. The study involved a purposive sample of 15 certified swimming coaches, all of whom participated in a four-week training intervention composed of 24 structured sessions. The training incorporated both dry-land and aquatic components and was grounded in high-intensity interval training principles. To measure outcomes, the Nelson motor response speed test was administered before and after the intervention. The results showed a statistically significant enhancement in motor response speed, with a 0.7-second improvement between pre- and post-tests. These findings support the hypothesis that a targeted training program can yield measurable physical benefits in a relatively short period. The implications of this study suggest that integrating similar training modules into professional development curricula for coaches and lifeguards could significantly raise the safety standards in aquatic settings.